Modeling of 6 to 4 Switched Reluctance Motor using Coefficient Method and Analytical Method - Kasrul Abd Karim; N. Abdullah; M. Nazri Othman; Auzani Jidin; RN Firdaus (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Electric kick scooter field has become famous this lately, and become another solution for electric vehicle. Switched Reluctance Motor has been choosen as the propulsion system in this application due to the advantages of this motor. Meanwhile, the issue of lack experience in electrical motor design is one of the hollow subjects in machine design field. Through design aspects, the Switched Reluctance motor is developed using a simple technique which is coefficients method. This method is to provide the easiest ways for other non-academic designer for those who has lack experience in motor design. A set of a coefficient to determine motor dimension is being set. Then, this technique will be refered to the existing analytical method to provide a design guideline and to validate this coefficient as the quick references to design the SRM. The aim is not to make a comparison between the methods but intend to provide another easiest solution to design the SRM motor. The modelling has been test using RMxprt tools The expectation from this method is the outcomes will be compatible with existing design.